2014
DOI: 10.1007/s00540-014-1843-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac damage after carotid intervention: a meta-analysis after a decade of randomized trials

Abstract: Compared to open surgery, CAS is associated with significantly decreased risk for symptomatic and asymptomatic cardiac damage postoperatively. Therefore, a standardized troponin measurement after CEA should be further evaluated in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…A meta-analysis of seven observational studies and two RCTs (5959 patients) observed that CAS was associated with a significant reduction in ECG diagnosed MI or non-ST elevation MI (NSTEMI) with troponin elevation (OR 0.37, 95% CI 0.22e0.61, p ¼ .0001). 201 The significance of perioperative MI (especially NSTEMI with biomarker elevation) has been a source of controversy since its inclusion within the primary endpoint in SAPPHIRE and CREST. 104,189 The rationale for including perioperative MI was because historical studies had suggested that it was associated with poorer long-term survival.…”
Section: Survival Following Perioperative Stroke or Myocardial Infarcmentioning
confidence: 99%
“…A meta-analysis of seven observational studies and two RCTs (5959 patients) observed that CAS was associated with a significant reduction in ECG diagnosed MI or non-ST elevation MI (NSTEMI) with troponin elevation (OR 0.37, 95% CI 0.22e0.61, p ¼ .0001). 201 The significance of perioperative MI (especially NSTEMI with biomarker elevation) has been a source of controversy since its inclusion within the primary endpoint in SAPPHIRE and CREST. 104,189 The rationale for including perioperative MI was because historical studies had suggested that it was associated with poorer long-term survival.…”
Section: Survival Following Perioperative Stroke or Myocardial Infarcmentioning
confidence: 99%
“…This difference between symptomatic and asymptomatic patients is also observed among patients undergoing CEA or tfCAS. 5 However, no difference was found when the study with the largest size effect on the analysis was left out. Hence, this study by Schermerhorn et al evaluated patients from the VQI registry and was not a prospectively designed study.…”
Section: Discussionmentioning
confidence: 99%
“…Open surgery is associated with higher surgical stress, and this could be the cause of the higher cardiac risk compared with stenting. 5 Moreover, carotid bifurcation and plaque manipulation during CEA increase the risk of thromboembolic events 6 as well as the risk of cranial nerve injuries. 7 On the other hand, manipulations with wires and endovascular devices during tfCAS could dislodge debris from a calcified aortic arch or cause dissections, leading to cerebrovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…within 30 days of surgery) in the study population was 3.6% (Table 3), which is considerably higher than the pooled incidence of 2.3% that was reported in a recent meta-analysis. 12 This difference can be explained by heterogeneity regarding study populations, MI definitions, and incorporation of routine post-operative biomarker assessment. For instance, the CREST trial which reported a MI incidence of 2.3% assessed cardiac biomarkers 6e8 hours after surgery and used a definition of post-operative MI that allowed for use of creatinine kinase MB fraction (CK-MB).…”
Section: Discussionmentioning
confidence: 99%